Analisis Strategi Kompetitif dan Kelayakan Bisnis Adreena Shoes dalam Menghadapi Persaingan Industri Sepatu Online - Rafik Yusup; Hani Humaeriyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the competitive strategy and business feasibility of Adreena Shoes amidst the fierce competition in the digital footwear market. While the industry offers massive opportunities, the low barrier to entry has created a saturated market. Using a descriptive qualitative approach, this research dissects how Adreena Shoes navigates this landscape through differentiation and multi-aspect feasibility analysis. The findings reveal that Adreena Shoes successfully occupies a strategic "middle ground" between luxury retail brands and conventional market traders. The combination of premium local materials from Cibaduyut and real-time interaction via Live Streaming serves as a primary driver for building digital trust. Technically and operationally, the adoption of marketplace technology and the roadmap for formalization through the OSS system confirm that this business is not only feasible but also poised for sustainable growth.